Implementasi Program Bantuan Stimulan Perumaha Swadaya Di Kecamatan Bajeng Barat Kabupaten Gowa - Nirwanasari, Nirwanasari; Fatmawati, Fatmawati; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to explain the  implementation of the Self-Help Housing Stimulant Assistance Program in West Bajeng District, Gowa Regency. This  study used qualitative research with data collection techniques used,  the instruments of interview, observation and literature study. The data was analyzed intractively andcontinuously. The results of this study showed that the implementation had not been maximally. It was seen from three indicators, namely the organization in this program was not clear and the implementer did not carry out their duties, the interpretations of the implementers were different because they were not given full guidance and  clear technical in implementing instructions and there was still miss communication  implementers and recipients of assistance, implementation did not have clear procedures and uncertain schedule of activities. Keywords: Assistance Program, Policy Implementation